2019
DOI: 10.1038/s41598-019-45510-7
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro pressure model towards studying the response of primary retinal ganglion cells to elevated hydrostatic pressures

Abstract: Glaucoma is a leading cause of blindness characterized by progressive degeneration of retinal ganglion cells (RGCs). A well-established risk factor for the development and progression of glaucoma is elevation of intraocular pressure (IOP). However, how elevated IOP leads to RGC degeneration remains poorly understood. Here, we fabricate a facile, tunable hydrostatic pressure platform to study the effect of increased hydrostatic pressure on RGC axon and total neurite length, cell body area, dendritic branching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…On the other hand, the relationship between IOP increases and RGC degeneration remains to be clarified. For instance, pressure levels of 25 mmHg have been recently reported as the threshold above which RGCs begin to degenerate [68], while IOP higher than 21/22 mmHg has been generally reported as a critical level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the relationship between IOP increases and RGC degeneration remains to be clarified. For instance, pressure levels of 25 mmHg have been recently reported as the threshold above which RGCs begin to degenerate [68], while IOP higher than 21/22 mmHg has been generally reported as a critical level.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of in vitro 3D/engineered models of glaucoma pathophysiology have emerged in recent years, most address the biology of the trabecular meshwork and regulation of intra-ocular pressure, or how this affects retinal ganglion cells [ 38 40 ]. Nevertheless, such models have demonstrated that 3D cultures are better at reproducing the pathophysiology of the disease, and better mimic in vivo behaviour, for example in terms of the cell responses to stress [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IOP is the main risk factor of glaucoma and, together with other factors, it has been implicated in RGC degeneration and death [71]. Several in vitro models have been developed [72] and allowed the demonstration that there are pressure-dependent changes in the length of axons and neurites of RGCs [73]. When cultures of RGCs are challenged with elevated pressure there is a severe impact in axon length and in the total neurite length, with a weakened neurite extension (Figure 3), without interfering with cell body area [73].…”
Section: Obstacles To Rgc Survival and Regeneration Upon Injury: Insimentioning
confidence: 99%
“…Several in vitro models have been developed [72] and allowed the demonstration that there are pressure-dependent changes in the length of axons and neurites of RGCs [73]. When cultures of RGCs are challenged with elevated pressure there is a severe impact in axon length and in the total neurite length, with a weakened neurite extension (Figure 3), without interfering with cell body area [73]. In glaucoma, the increased IOP perturbs anterograde and retrograde axonal transports that lead to deprivation of RGCs of neurotrophic factors produced by brain targets [74].…”
Section: Obstacles To Rgc Survival and Regeneration Upon Injury: Insimentioning
confidence: 99%